Retinitis Pigmentosa patients treated with ozone therapy during 20 years. Cuban experiences (Ozone Therapy Global Journal, 2011)
Retinitis Pigmentosa (RP) is characterized by bad night vision, decrease of visual fieldand/or acuity, with electroretinogram (ERG) diminished in amplitude and finally, nonreproducible. Taking into account some of the ozone biological effects, as: improvementin the oxygen metabolism, increase in the cell energy, the immunomodulator capacityand enhancement of the antioxidant defense system the aim of this paper is to assessozone therapy’s efficacy i n these patients, treated twice a yea r during 20 years . Acont r olled and retrospect i ve clin i cal s tudy was performed in 56 patients with TypicalRetinitis Pigme ntosa (non-associa ted) , with sample homogeneity, in age, sex andstage of the disease, and with signed informed consent. Forty patients received ozonedaily, by rectal way, during 20 sessions (at a concentration of 40 mg/L and a volumeof 200 mL) as only treatment, w i th repe tition of this cy cle every 6 m onths, a nd 16rec e i ved other medical treatmen ts (control group). Resul ts showed that , after 10years, patients in stages I and II h ad a better r esp onse to ozone therap y, a nd th i sresponse was more la sting, with an improvement attained as of 4 months, which isthe shortest time period for patients in stages II and IV. After 20 years of treatment,50.1 % of patients improved their visual field, 31.1 % remained the same and 18 %followed the course of the disease. In respect to visual acuity, we observed that 37.5%of patients improved, 34.9 % remained stable and 27.6 % continued the course of thedisease. It is recommended to apply ozone therapy at six-month intervals in order todelay the course of the disease and maintain the visual capabilities. No side effectswere observed. Ozone therapy is a good therapeutic choice in the treatment of patientswith RP increasing their quality of life.